Chestnut tannin induces gut degeneration in Aedes albopictus mosquito larvae - Linda Abenaim; Priscilla Farina; Angela Rosa Cuzzola; Loretta Guidi; Romano Dallai; David Mercati; Erika Carla Pierattini; Barbara Conti; Alessandro Mandoli (Environmental Science and Pollution Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

Mediating role of proteomics in the association between per- and polyfluoroalkyl substance exposure and blood pressure in youth - Jiawen Carmen Chen; Jesse A. Goodrich; Jiawen Liao; Shiwen Li; Qiran Jia; Douglas I. Walker; Elizabeth Costello; Tanya L. Alderete; Michael I. Goran; Damaskini Valvi; Shudi Pan; Brittney O. Baumert; et al. (Environmental Pollution, 2025)

Are environmental factors correlated with the diversity of Phytophthora in organically and conventionally managed citrus orchards in Sicily? Insights from metabarcoding and baiting - Sebastiano Conti Taguali; Federico La Spada; Antonella Pane; Peter J. A. Cock; Beatrix Keillor; David E. L. Cooke; Santa Olga Cacciola (Mycological Progress, 2025)
Phytophthora species pose a significant threat to citrus production in the Mediterranean, particularly in Sicily, a major citrus-producing region. This study explores the diversity and distribution of Phytophthora taxa in Sicilian citrus orchards, addressing the urgent need to tackle increasing agricultural challenges, such as climate change. Specifically, it aimed to evaluate how environmental factors, such as the type of management (organic vs. conventional) and geographical area influence the composition of Phytophthora communities in Sicilian citrus orchards, and whether these communities correlate with tree health. An additional objective was to compare the effectiveness of traditional baiting and high-throughput metabarcoding techniques (targeting the ITS1 region and RPS10 gene) in capturing this diversity, as well as to assess potential shifts in community structure resulting from climate change by comparing current data with historical records. Soil samples were collected from ten citrus-producing areas under two distinct agronomic management and tree health conditions. Traditional baiting recovered 556 isolates of three already described Phytophthora species, while ITS1 metabarcoding identified ten additional taxa, demonstrating higher specificity (99.5% of ITS1 reads classified as Phytophthora compared to 82.5% for RPS10 ). Our findings indicate that geographical location is a key driver of community composition. Although statistical analyses did not reveal significant differences in Phytophthora diversity between organic and conventional management systems, these results provide valuable insights into the factors shaping pathogen communities. These insights are crucial for developing targeted disease management strategies and for understanding how environmental stressors, including climate change, impact pathogen dynamics in Mediterranean citrus orchards. Graphical Abstract

Unveiling the invisible threat: cutting-edge methods for detecting fungal and oomycete plant pathogens and mycotoxins - Rossana Parlascino; Sebastiano Conti Taguali; Mario Riolo; Moricca Salvatore; József Bakonyi; David Ezra; Alessandra Benigno; Federico La Spada; Antonella Pane; Santa Olga Cacciola (Physiological and Molecular Plant Pathology, 2025)

Short-chain per- and polyfluoroalkyl substances associate with elevated alanine aminotransferase: Cross-sectional analysis results from the STRIVE cohort - Bojung Seo; Hongxu Wang; Rachel Maguire; Yukun Liu; Beatrice Smith; Kristin Haller; Marjorie Riggan; David V. Conti; Heinz-Josef Lenz; Kara Wegermann; Antonio Planchart; Giorgio Roccaro; et al. (Environmental Research, 2025)

Exploring the plastivorous activity of Hermetia illucens (Diptera Stratiomyidae) larvae - Linda Abenaim; David Mercati; Alessandro Mandoli; Joachim Carpentier; Grégoire Noël; Barbara Conti; Rudy Caparros Megido; Romano Dallai (Environmental Science and Pollution Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Oxidative gaseous air pollutant exposure interacts with PNPLA3-I148M genotype to influence liver fat fraction and multi-omics profiles in young adults - William B. Patterson; Nathan D. Young; Elizabeth A. Holzhausen; Frederick Lurmann; Donghai Liang; Douglas I. Walker; Dean P. Jones; Jiawen Liao; Zhanghua Chen; David V. Conti; Lida Chatzi; Jesse A. Goodrich; et al. (Environmental Pollution, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

The potential mediating role of the gut microbiome and metabolites in the association between PFAS and kidney function in young adults: A proof-of-concept study - Hailey E. Hampson; Shiwen Li; Douglas I. Walker; Hongxu Wang; Qiran Jia; Sarah Rock; Elizabeth Costello; Petter Bjornstad; Laura Pyle; Jonathan Nelson; Frank D. Gilliland; Zhanghua Chen; et al. (Science of The Total Environment, 2024)

Exposure to per- and polyfluoroalkyl substances and alterations in plasma microRNA profiles in children - Yijie Li; Brittney O. Baumert; Nikos Stratakis; Jesse A. Goodrich; Haotian Wu; Shelley H. Liu; Hongxu Wang; Emily Beglarian; Scott M. Bartell; Sandrah Proctor Eckel; Douglas Walker; Damaskini Valvi; et al. (Environmental Research, 2024)

Weak phylogenetic effect on specialist plant assemblages and their persistence on habitat islands - Adam Klimeš; Rafael Molina‐Venegas; Angelino Carta; Milan Chytrý; Luisa Conti; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; Francisco E. Méndez‐Castro; David Zelený; et al. (Journal of Biogeography, 2024)
Aim The influence of species phylogenetic relatedness on the formation of insular assemblages remains understudied in functional island biogeography, especially for terrestrial habitat islands (i.e. distinct habitat patches embedded in a matrix that differ in the prevailing environmental conditions). Here, we tested three eco‐evolutionary hypotheses: (1) functional specialization of species (i.e. specialism) is associated with phylogenetic clustering at the habitat archipelago scale, (2) such clustering increases with insularity at the habitat island scale and (3) traits indicative of effective local persistence strategies shape island specialism. Location Terrestrial habitat islands, Europe (Fens in the Western Carpathians, Outcrops in Moravia and Mountaintops in the Cantabrian Range). Taxon Angiosperms. Methods We assessed the phylogenetic relatedness of habitat specialists in three different archipelagos composed of terrestrial habitat islands based on phylogenetic signals and phylogenetic diversity (PD) measures. We estimated the effect of insularity on PD using linear models and the effect of persistence traits on specialism using phylogenetic logistic regressions. Results Our hypotheses were largely not supported. Outcrop and mountaintop specialist assemblages did not exhibit any phylogenetic structuring, whereas fen specialists were clustered at the archipelago scale. Therefore, insularity seems not to act as a selective force for phylogenetic structure, and ecologically important persistence traits do not operate as precursors of specialism. Main Conclusions Our results show that species phylogenetic relatedness plays a minor role in shaping habitat island specialist assemblages. Furthermore, the effects of phylogenetic relatedness on assemblages of island specialists are system and scale dependent. Finally, accounting for species' phylogenetic relatedness on persistence traits yielded results similar to previous studies, which corroborates the positive relationship between insularity and functional traits (indicative of enhanced plant persistence abilities with increasing within‐archipelago insularity).

Environmental pollutant risk factors for worse COVID-19 related clinical outcomes in predominately hispanic and latino populations - Brittney O. Baumert; Hongxu Wang; Shar Samy; Sung Kyun Park; Chun Nok Lam; Kathryn Dunn; Brismar Pinto-Pacheco; Douglas Walker; Julio Landero; David Conti; Leda Chatzi; Howard Hu; et al. (Environmental Research, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Exposure to perfluoroalkyl substances and longitudinal changes in bone mineral density in adolescents and young adults: A multi-cohort study - Emily Beglarian; Elizabeth Costello; Douglas I. Walker; Hongxu Wang; Tanya L. Alderete; Zhanghua Chen; Damaskini Valvi; Brittney O. Baumert; Sarah Rock; Bruna Rubbo; Max T. Aung; Frank D. Gilliland; et al. (Environmental Research, 2024)

Per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers and dysregulation of MicroRNA expression in humans and animals—A systematic review - Yijie Li; Brittney O. Baumert; Elizabeth Costello; Jiawen Carmen Chen; Sarah Rock; Nikos Stratakis; Jesse A. Goodrich; Yinqi Zhao; Sandrah P. Eckel; Douglas I. Walker; Damaskini Valvi; Michele A. La Merrill; et al. (Environmental Research, 2024)

Excess pancreatic cancer risk due to smoking and modifying effect of quitting smoking: The Multiethnic Cohort Study - David Bogumil; Daniel Stram; Dale L. Preston; Stephen J. Pandol; Anna H. Wu; Roberta McKean-Cowdin; David V. Conti; Veronica Wendy Setiawan (Cancer Causes & Control, 2024)
Purpose Risk factors for pancreatic cancer include racial/ethnic disparities and smoking. However, risk trajectories by smoking history and race/ethnicity are unknown. We examined the association of smoking with pancreatic cancer by race/ethnicity to generate age-specific incidence estimates by smoking history. Methods We modeled pancreatic cancer incidence by race/ethnicity, age, pack-years, and years-quit using an excess relative risk model for 182,011 Multiethnic Cohort participants. We tested heterogeneity of smoking variables and pancreatic cancer by race/ethnicity and predicted incidence by smoking history. Results We identified 1,831 incident pancreatic cancer cases over an average 19.3 years of follow-up. Associations of pack-years ( p interaction by race/ethnicity = 0.41) and years-quit ( p interaction = 0.83) with pancreatic cancer did not differ by race/ethnicity. Fifty pack-years smoked was associated with 91% increased risk (95% CI 54%, 127%) relative to never smokers in the combined sample. Every year quit corresponded to 9% decreased excess risk (95% CI 2%, 15%) from pack-years smoked. Differences in baseline pancreatic cancer risk across racial/ethnic groups ( p < 0.001) translated to large differences in risk for smokers at older ages across racial/ethnic groups (65–122 cases per 100,000 at age 70). Conclusion Smoking pack-years were positively associated with elevated pancreatic cancer risk. Predicted risk trajectories showed a high impact of smoking cessation at < 65 years. Although we did not identify significant heterogeneity in the association of pack-years or years quit with pancreatic cancer risk, current smoker risk varied greatly by race/ethnicity in later life due to large differences in baseline risk.

Prioritizing conservation of terrestrial orchids: A gap analysis for Italy - Michele Lussu; Leonardo Ancillotto; Rocco Labadessa; Michele Di Musciano; Piero Zannini; Riccardo Testolin; Francesco Santi; David Dolci; Matteo Conti; Michela Marignani; Stefano Martellos; Lorenzo Peruzzi; et al. (Biological Conservation, 2024)

Associations of per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers with oxidative stress markers: A systematic review and meta-analysis - Jiawen Carmen Chen; Brittney O. Baumert; Yijie Li; Yiping Li; Shudi Pan; Shante Robinson; Bruna Rubbo; Elizabeth Costello; Jie He; Hailey Hampson; Emily Beglarian; Sarah Rock; et al. (Environmental Research, 2023)

Ambient temperature and air pollution associations with suicide and homicide mortality in California: A statewide case-crossover study - Md Mostafijur Rahman; Melissa Lorenzo; George Ban-Weiss; Zainab Hasan; Mehjar Azzouz; Sandrah P. Eckel; David V. Conti; Fred Lurmann; Hannah Schlaerth; Jill Johnston; Joseph Ko; Lawrence Palinkas; et al. (Science of The Total Environment, 2023)

Effect of sow mass vaccination against Mycoplasma hyopneumoniae on the humoral immune response of newborn piglets - Elisa Rigo De Conti; Karine Ludwig Takeuti; Aparecida Tatiane Lino Fiúza; Laura Lopes de Almeida; David Emilio Santos Neves de Barcellos; Fernando Pandolfo Bortolozzo (Tropical Animal Health and Production, 2022)

Correction: International Regulatory Collaboration on the Analysis of Nitrosamines in Metformin-Containing Medicines - David A. Keire; Robert Bream; Uwe Wollein; Schmaler-Ripcke; Annette Burchardt; Massimiliano Conti; Adam Zmysłowski; Peter Keizers; Justin Morin; Jalene Poh; Mark George; Michael Wierer (The AAPS Journal, 2022)

International Regulatory Collaboration on the Analysis of Nitrosamines in Metformin-Containing Medicines - David A. Keire; Robert Bream; Uwe Wollein; Jeannette Schmaler-Ripcke; Annette Burchardt; Massimiliano Conti; Adam Zmysłowski; Peter Keizers; Justin Morin; Jalene Poh; Mark George; Michael Wierer (The AAPS Journal, 2022)
Recalls of some batches of metformin have occurred due to the detection of N -nitrosodimethylamine (NDMA) in amounts above the acceptable intake (AI) of 96 ng per day. Prior to the recalls, an international regulatory laboratory network had been monitoring drugs for nitrosamine impurities with each laboratory independently developing and validating multiple analytical procedures to detect and measure nitrosamines in metformin drugs used in their jurisdictions. Here, we provide an overview of the analysis of metformin active pharmaceutical ingredients (APIs) and drug products with 1090 samples (875 finished dosage forms (FDFs) and 215 API samples) tested beginning in November of 2019 through July of 2020. Samples were obtained internationally by a variety of approaches, including purchased, received from firms via information requests or selected by regional regulatory authorities (either at wholesalers or during GMP inspections). Only one nitrosamine (NDMA) was detected and was only present in some batches of metformin products. For API samples, 213 out of 215 lots tested had no measurable level of NDMA. For FDF samples tested, the number of batches with NDMA above the AI amount for patient safety was 17.8% (156/875). Based on these data, although the presence of NDMA was of concern, 82.2% of the samples of metformin drug products tested met quality and safety standards for patients. Regulatory agencies continue to collaborate extensively and work with marketing authorization holders to understand root causes of nitrosamine formation and agree on corrective actions to mitigate the presence of NDMA in future metformin batches. Graphical abstract

Insularity promotes plant persistence strategies in edaphic island systems - Luisa Conti; Francisco E. Méndez‐Castro; Milan Chytrý; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; David Zelený; Gianluigi Ottaviani (Global Ecology and Biogeography, 2022)
Aim Trait‐based approaches are being used increasingly in island biogeography, providing key insights into the eco‐evolutionary dynamics of insular systems. However, the determinants of persistence of plant species after they have arrived and established on an island remain largely unexplored. Here, we used three edaphic island systems (i.e., habitat patches distinguished from the landscape matrix by distinct soil conditions and specialized vegetation) to examine relationships between persistence strategies (those associated with clonality, bud bank, seed mass and life‐form) and insularity. We hypothesized that insularity promotes and selects strategies to persist locally, such that species occurring on small and/or isolated edaphic islands show trait values indicative of enhanced persistence and lower functional diversity. Location Three European systems of edaphic islands in the Western Carpathians, Moravia and the Cantabrian Range. Time period Present. Major taxa studied Vascular plants. Methods For each system, we used linear models to explore persistence‐related plant trait patterns (mean trait values and functional diversity) in relationship to three insularity metrics (island size, isolation and target effect). We focused on patterns of edaphic island specialists because their presence is confined to the islands. Results We found that insularity metrics largely explained the variation of the mean value and diversity of persistence‐related traits of edaphic island plant specialists. Specifically, insularity was positively related to traits supporting local persistence (e.g., more extensive lateral spread) and to a reduced variability in persistence traits. More insular systems showed stronger and more numerous trait–insularity links. Main conclusions Insularity can affect plant species diversity, form and function in edaphic island systems, such as selecting for enhanced and less diverse persistence strategies. Plant species occurring in insular systems might therefore avoid or delay local extinction by promoting adaptive strategies to persist in situ .

Populations of a widespread hexacoral have trophic plasticity and flexible syntrophic interactions across the Indo-Pacific Ocean - Maria Eduarda Alves Santos; David Michael Baker; Inga Elizabeth Conti-Jerpe; James Davis Reimer (Coral Reefs, 2021)

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Porosity Estimation and Geometric Characterization of Fractured and Karstified Carbonate Rocks Using GPR Data in the Salitre Formation, Brazil - Iurianne M. M. Conti; David L. de Castro; Francisco H. R. Bezerra; Caroline L. Cazarin (Pure and Applied Geophysics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Whale Shark Tourism: Impacts on Coral Reefs in the Philippines - C. W. Martin Wong; Inga Conti-Jerpe; Laurie J. Raymundo; Caroline Dingle; Gonzalo Araujo; Alessandro Ponzo; David M. Baker (Environmental Management, 2019)

Is musculoskeletal pain a consequence or a cause of occupational stress? A longitudinal study - Matteo Bonzini; Lorenza Bertu’; Giovanni Veronesi; Marco Conti; David Coggon; Marco M. Ferrario (International Archives of Occupational and Environmental Health, 2015)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genetic contribution of the leukotriene pathway to coronary artery disease - Jaana Hartiala; Dalin Li; David V. Conti; Susanna Vikman; Yesha Patel; W. H. Wilson Tang; Marie-Louise Brennan; John W. Newman; Charles B. Stephensen; Patrice Armstrong; Stanley L. Hazen; Hooman Allayee (Human Genetics, 2011)

Variation in folate pathway genes and distal colorectal adenoma risk: a sigmoidoscopy-based case–control study - A. Joan Levine; Won Lee; Jane C. Figueiredo; David V. Conti; David J. Vandenberg; Brian D. Davis; Christopher K. Edlund; Susanne M. Henning; David Heber; Mariana C. Stern; Robert W. Haile (Cancer Causes & Control, 2011)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

Intercellular adhesion molecule-1 and childhood asthma - Yu-Fen Li; Yo-Hsuang Tsao; W. James Gauderman; David V. Conti; Edward Avol; Louis Dubeau; Frank D. Gilliland (Human Genetics, 2005)

Genetic Analysis of Neoplasia Induced by N-Nitroso-N-methylurea in Xiphophorus Hybrid Fish - Steven Kazianis; Irma Gimenez-Conti; David Trono; Anthony Pedroza; Lori B. Chovanec; Donald C. Morizot; Rodney S. Nairn; Ronald B. Walter (Marine Biotechnology, 2001)

Phylogenetic relationships and character evolution in Primula L.: The usefulness of ITS sequence data - Elena Conti; Erik Suring; David Boyd; Janet Jorgensen; Jason Grant; Sylvia Kelso (Plant Biosystems, 2000)